2015
DOI: 10.2196/medinform.4450
|View full text |Cite
|
Sign up to set email alerts
|

Technology for Large-Scale Translation of Clinical Practice Guidelines: A Pilot Study of the Performance of a Hybrid Human and Computer-Assisted Approach

Abstract: BackgroundThe construction of EBMPracticeNet, a national electronic point-of-care information platform in Belgium, began in 2011 to optimize quality of care by promoting evidence-based decision making. The project involved, among other tasks, the translation of 940 EBM Guidelines of Duodecim Medical Publications from English into Dutch and French. Considering the scale of the translation process, it was decided to make use of computer-aided translation performed by certificated translators with limited experti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Back-translation was conducted by one bilingual translator and another translation software. By using the software, we can assess the quality of wording that is generated during an automated literal translation without any background bias [24]. Our translation team compared and evaluated two back-translation sources to confirm accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Back-translation was conducted by one bilingual translator and another translation software. By using the software, we can assess the quality of wording that is generated during an automated literal translation without any background bias [24]. Our translation team compared and evaluated two back-translation sources to confirm accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, several additional healthcare-related studies have been kindly suggested by Meng Ji, co-author of this volume: Van de Velde et al (2015); Thonon et al (2021); Chen et al (2017);and Turner et al (2019).…”
Section: Some Additional Linksmentioning
confidence: 99%
“…Along this line of consideration, the core issue affecting the quality of machine translation is the machine's performance to deal with ambiguities based on employing appropriate phrase identification. To be specific, structural ambiguity is one of the most complex ones, and previous researchers studied this phenomenon from multiple angles and proposed a variety of methods for phrase identification and disambiguation [3].…”
Section: Introductionmentioning
confidence: 99%